z UJI DAYA HASIL STEK PUCUK KENTANG (Solanum tuberosum L.) PADA BERBAGAI JARAK TANAM DI DATARAN MEDIUM - tutik zaerurrohmi (CROP AGRO, Scientific Journal of Agronomy, 2020)
The aim of this experiment was to investigate the yield potential of potato shoot cutting planted in several planting spaces at medium plain. The experiment was conducted from June to September 2018, at Beririkjarak Village, Wanasaba District, East Lombok Regency, with the altitude of 500 m asl. The experiment was arranged in Randomized Block Design (RBD) with two factors and three replications. The first factor was spacing between rows, consisted of three levels, namely: A1=20 cm, A2=30 cm, A3=40 cm, and the second factor was spacing within rows, namely: D1=20 cm, D2=25 cm, D3=30 cm. Data collected were analyzed by using Analysis of Variance at 5% level. The parameters which showed significant effects were tested further with Honestly Significant Difference (HSD) at the 5% level. There were several results of the experiment, as follows: The potato shoot cuttings planted in medium altitude were not affected by planting space between rows and within rows. There was an interaction between planting space between rows and within rows on plant height at 4 wap, number of leaves at 2 wap, number of primary branches at 2 wap and tuber weight per plot. Planting space between rows showed no effect on all growth and yields parameters of potato. Plating space within row affected plant height at 4 wap, but did not affect the yield of potato.